A portable renewable solar energy-powered cooling system based on wireless power transfer for a vehicle cabin. (1st June 2017) - Pan, Hongye; Qi, Lingfei; Zhang, Xingtian; Zhang, Zutao; Salman, Waleed; Yuan, Yanping; Wang, Chunbai
Graphical abstract: Highlights: A novel portable solar collector mechanism is optimally designed. Wireless power transfer is first applied to cooling systems. A supercapacitor stores electricity and outputs a regulated supply. The proposed cooling system shows high efficiency in a limited space. Abstract: As the greenhouse effect becomes increasingly serious, cooling a vehicle cabin parked under the blazing sun without running the engine or using an electric vehicle's power has received considerable attention. In this paper, we develop a novel portable, renewable, solar energy-powered cooling system with wireless power transfer (WPT) and supercapacitors to cool the vehicle cabin. The proposed system consists of a solar collector mechanism, an energy conduit, and a temperature control and cooling module. First, consisting of folding solar photovoltaic (PV) panels, the solar collector mechanism making the proposed system portable. Once collected, the solar energy is converted into electricity and stored in the supercapacitors through wireless power transfer without breaching the vehicle body. Automatic temperature regulation is achieved with the cooling device via the temperature control and cooling module. The experimental results indicate that a maximum output power of 2.181 W and a maximum WPT efficiency of 60.3% are achieved when the prototype loaded with 3 Ω and 5 Ω respectively. Meanwhile, the simulation shows the temperature inside the cabin is reduced by as much as 4.2 °C in average, demonstrating that the proposed solar energy-powered cooling system is effective and feasible in cooling a hot vehicle cabin.